VALIDATION OF REAL-TIME REVERSE TRANSCRIPTION POLYMERASE CHAIN REACTION FOR INDIRECT ASSESSMENT OF FMD VIRUS TITRE - D. A. Lozovoy; M. I. Doronin; V. A. Starikov; D. V. Mikhalishin; A. A. Shishkova; A. M. Timina; A. B. Borisov (Ветеринария сегодня)
Procedure for validation of the method for indirect assessment of cultural FMD virus titre (T FMDV) in raw materials used for vaccine production with real time reverse transcription polymerase chain reaction (RT-PCRrt) based on determined amplifcation threshold cycle value (Ct) using linear regression model, TFMDV= –0.2956Ct+ 11.4650, is described in the paper. Testing results for 390 samples of cultural FMD virus were analyzed and basic validation characteristics of the proposed method: specifcity, accuracy, precision, limit of detection and limit of quantifcation, application scope and linearity, were defned. Validation results for the method for indirect assessment of FMD virus titre with RT-PCRrt met the acceptance criteria.